CpG Island Methylation in Sessile Serrated Adenoma/Polyp of the Colorectum: Implications for Differential Diagnosis of Molecularly High-Risk Lesions among Non-dysplastic Sessile Serrated Adenomas/Polyps - Ji Ae Lee; Hye Eun Park; Seung-Yeon Yoo; Seorin Jeong; Nam-Yun Cho; Gyeong Hoon Kang; Jung Ho Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background Although colorectal sessile serrated adenomas/polyps (SSA/Ps) with morphologic dysplasia are regarded as definite high-risk premalignant lesions, no reliable grading or risk-stratifying system exists for non-dysplastic SSA/Ps. The accumulation of CpG island methylation is a molecular hallmark of progression of SSA/Ps. Thus, we decided to classify non-dysplastic SSA/Ps into risk subgroups based on the extent of CpG island methylation. Methods The CpG island methylator phenotype (CIMP) status of 132 non-dysplastic SSA/Ps was determined using eight CIMP-specific promoter markers. SSA/Ps with CIMP-high and/or MLH1 promoter methylation were regarded as a high-risk subgroup. Results Based on the CIMP analysis results, methylation frequency of each CIMP marker suggested a sequential pattern of CpG island methylation during progression of SSA/P, indicating MLH1 as a late-methylated marker. Among the 132 non-dysplastic SSA/Ps, 34 (26%) were determined to be high-risk lesions (33 CIMP-high and 8 MLH1-methylated cases; seven cases overlapped). All 34 high-risk SSA/Ps were located exclusively in the proximal colon (100%, p = .001) and were significantly associated with older age (≥ 50 years, 100%; p = .003) and a larger histologically measured lesion size (> 5 mm, 100%; p = .004). In addition, the high-risk SSA/Ps were characterized by a relatively higher number of typical base-dilated serrated crypts. Conclusions Both CIMP-high and MLH1 methylation are late-step molecular events during progression of SSA/Ps and rarely occur in SSA/Ps of young patients. Comprehensive consideration of age (≥ 50), location (proximal colon), and histologic size (> 5 mm) may be important for the prediction of high-risk lesions among non-dysplastic SSA/Ps.